Expanded Hemodialysis ameliorates uremia-induced impairment of vasculoprotective KLF2 and concomitant proinflammatory priming of endothelial cells through an ERK/AP1/cFOS-dependent mechanism - Zhao, Hongfan; Wu, Dashan; Gyamfi, Michael Adu; Wang, Pinchao; Luecht, Christian; Pfefferkorn, Anna Maria; Ashraf, Muhammad Imtiaz; Kamhieh-Milz, Julian; Witowski, Janusz; Dragun, Duska; Budde, Klemens; Schindler, Ralf; et al. (Frontiers in Immunology, 2023)
Aims: Expanded hemodialysis (HDx) therapy with improved molecular cut-off dialyzers exerts beneficial effects on lowering uremia-associated chronic systemic microinflammation, a driver of endothelial dysfunction and cardiovascular disease (CVD) in hemodialysis (HD) patients with end-stage renal disease (ESRD). However, studies on the underlying molecular mechanisms are still at an early stage. Here, we identify the (endothelial) transcription factor Krüppel-like factor 2 (KLF2) and its associated molecular signalling pathways as key targets and regulators of uremia-induced endothelial micro-inflammation in the HD/ESRD setting, which is crucial for vascular homeostasis and controlling detrimental vascular inflammation.Methods and results: First, we found that human microvascular endothelial cells (HMECs) and other typical endothelial kidney model cell lines (e.g. HUVECs, HREC, and HEK) exposed to uremic serum from patients treated with two different hemodialysis regimens in the Permeability Enhancement to Reduce Chronic Inflammation (PERCI-II) crossover clinical trial -comparing High-Flux (HF) and Medium Cut-Off (MCO) membranes -exhibited strongly reduced expression of vasculoprotective KLF2 with HF dialyzers, while dialysis with MCO dialyzers led to the maintenance and restoration of physiological KLF2 levels in HMECs.Mechanistic follow-up revealed that the strong downmodulation of KLF2 in HMECs exposed to uremic serum was mediated by a dominant engagement of detrimental ERK instead of beneficial AKT signalling, with subsequent AP1-/c-FOS binding in the KLF2 promoter region, followed by the detrimental triggering of pleiotropic inflammatory mediators, while the introduction of a KLF2 overexpression plasmid could restore physiological KLF2 levels and downmodulate the detrimental vascular inflammation in a mechanistic rescue approach.Conclusions: Uremia downmodulates vasculoprotective KLF2 in endothelium, leading to detrimental vascular inflammation, while MCO dialysis with the novel improved HDx therapy can maintain physiological levels of vasculoprotective KLF2.